Fully Coupled Frictional Contact Using Elastic Halfspace Theory - Willner, Kai (Journal of Tribology, 2008)
The effect of dry metallic friction can be attributed to two major mechanisms: adhesion and ploughing. While ploughing is related to severe wear and degradation, adhesion can be connected to pure elastic deformations of the contacting bodies and is thus the predominant mechanism in a stable friction pair. The transmitted friction force is then proportional to the real area of contact. Therefore, a lot of effort has been put into the determination of the fraction of real area of contact under a given load. A broad spectrum of analytical and numerical models has been employed. However, it is quite common to employ the so-called Mindlin assumptions, where the contact area is determined by the normal load only, disregarding the influence of friction. In the subsequent tangential loading, usually the contact pressure distribution is kept fixed such that the coupling between the tangential and normal solutions is neglected. Here, a numerical solution scheme based on elastic halfspace theory for frictional contact problems is presented where full coupling between the normal and tangential tractions and displacements is taken into account. Several examples show the influence of the coupling effects, but also the limitations for the analysis of rough contacts. Copyright © 2008 by ASME.
UnivIS-Import:2015-03-09:Pub.2008.tech.FT.FT-TM.fullyc
Keywords: Elastic contact; Friction; Halfspace theory; Rough surfaces